Kesulitan-Kesulitan Siswa dalam Belajar Speaking English - A’am Rifaldi Khunaifi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
This study aims to answer the problems regarding the difficulties experienced by students in learning speaking English at the MAN Palangka Raya Class Model SchoolThe research method used in this research is Analitycal Research which takes a descriptive step of combining qualitative methods with quantitative methods. The population of this study were students of class XI.I.S-1 and XI.I.S-2 in MAN Palangka Raya Model which amounted to 65 students. Sampling, researchers used purposive sampling and used homogenous samples taken from one of six types of purposive sampling. The data collection method used is observation, interview, test and documentation.The results of this study indicate that the difficulties faced by the students of MAN Model of the class of xi.i.s class include: the interaction pattern is still simple, this is evidenced by the results of the scores without scores, because the patterns used by students for homogeneous and simple presentations.